Stereoselective synthesis and characterization of novel trans-4-(thiophenyl)pyrazolyl-β-lactams and their C–3 functionalization. Issue 33 (16th August 2019) - Saini, Preety; Bari, S.S.; Sahoo, Subash C.; Khullar, Sadhika; Mandal, Sanjay K.; Bhalla, Aman
Abstract: A stereoselective synthesis and C–3 functionalization of a long series of novel hybrid 4-(thiophenyl)pyrazolyl-β-lactams have been carried out. The divergent substrate scope and mechanistic insights were examined to delineate the generality of reaction that favored trans -β-lactams4a-q almost exclusively in all cases. The C–3 functionalization was achieved by Lewis acid assisted nucleophilic substitution reaction of cis -3-chloro-β-lactams6a-e to afford cis -3-monosubstituted-β-lactams7a-e . The cis stereochemistry of β-lactams7a-e was further established by stereospecific desulfurization with Raney-nickel, in representative cases (7a, b ), leading to the formation of cis -β-lactams8a, b . The structures and stereochemical assignments for synthesized β-lactams have been unambiguously confirmed using FT-IR, 1D NMR ( 1 H and 13 C), 2D NMR ( 1 H– 1 H COSY, 1 H– 13 C HSQC and 13 C DEPT–135), elemental analysis (CHN), mass spectrometry (ESI-MS) and single crystal X-ray crystallography, in representative cases (4b, e ). The cis and trans configuration of the hydrogen/chloro/nucleophile substituent at C–3 was assigned with respect C4–H of the β-lactam ring. Graphical abstract: Image 1 Highlights: Simple and efficient stereoselective synthesis of conformationally restricted trans -(thiophenyl)pyrazolyl-β-lactams. C–3 Functionalization and reductive desulfurization to access monosubstituted/disubstituted β-lactams. Structural elucidation and stereochemistry establishment of 4b and 4e by single crystal X-ray crystallographic studies. Exploration of steric bulk in the target β-lactams in relevance to mechanistic aspects.